Determinants of Venture Capital Supply in Sub-Saharan Africa - Olabanji Oni (Journal of Economics and Behavioral Studies, 2017)
The purpose of this paper is to determine the variables that influence venture capital supply in Sub-Sahara Africa. The study developed econometric models and examined a 10-year period (2006 to 2015) pertaining to eight (8) Sub-Sahara African countries namely: Botswana, Ivory Coast, Ghana, Kenya, Mauritius, Nigeria, South Africa and Uganda. The empirical model includes six determinants (initial public offering, market capitalisation, unemployment rate, foreign direct investment inflow, inflation rate and trade openness). Secondary data was utilised for the study. The primary sources of data were the World Bank Development indicators and Preqin data base. All the statistical analyses in the study were performed using E-views version 8. Panel data models of pooled, fixed and random effects were employed. The results suggest that there is a significant positive relationship between initial public offering, market capitalisation and venture capital supply. Second, there is no significant relationship between unemployment rate, foreign direct investment inflows, trade openness and venture capital supply. Based on the empirical findings, this study recommends that Sub-Sahara African governments should attempt to develop their economies by improving infrastructure and corporate governance. There is also a need for African countries to develop the equity market.